In Vitro Antifungal Activity of Streptomyces and Bacillus Isolates against Fusarium oxysporum f.sp. cubense - Nurhidayati, Febry; Wisanggeni, Gen Adi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Fusarium wilt disease caused by Fusarium oxysporum f.sp. cubense (Foc) represents a major constraint to banana production, leading to severe yield and quality losses. The use of biological control agents (BCAs) such as Streptomyces and Bacillus offers an environmentally sustainable alternative to manage this pathogen. This study aimed to evaluate the antagonistic activity, culture filtrate effects, volatile organic compounds, and compatibility of Streptomyces S01, Bacillus B01, and Bacillus B16 isolates against Foc under in vitro conditions. A completely randomized design (CRD) with three replications was employed. Results indicated that Streptomyces S01 was the most effective isolate, achieving 84.12% inhibition in the dual culture assay, 69.96% in the culture filtrate test, and 41.4% through volatile compound activity. Isolates Bacillus B16 and Bacillus B01 showed moderate efficacy, with Bacillus B16 exhibiting superior performance in the volatile assay (28.8%). Compatibility tests revealed that Streptomyces S01 + Bacillus B16 and Bacillus B01 + Bacillus B16 were mutually compatible, while Streptomyces S01 + Bacillus B01 displayed incompatibility. These findings suggest that Streptomyces S01, particularly in combination with Bacillus B16, holds strong potential as a microbial consortium for the biological control of Fusarium wilt in banana cultivation.